The Relationship between the Students English Speaking Skills and Their Closeness to English - Husna, Hawa Asma Ul (Universitas Negeri Semarang, 2021)
Speaking English skills is a frightening thing for some English for Foreign Language Learners (EFL), including students at one of the universities in Jakarta. Even though they live and stay in Jakarta and its surroundings, which is the capital city of Indonesia with high job competition, there are still many students who have a low level of English speaking skills. This study aims to determine the relationship between English speaking skills and their closeness to English as seen from the 5 levels of students' proficiency in speaking English. This research uses the descriptive qualitative method. The subjects of this study were 2 classes with a total of 60 students at a university in Jakarta in the 2019-2020 school year. Researchers used tests, questionnaires, interviews, and literature studies as data collection techniques. While the data analysis technique used by researchers is using data triangulation. The results of this study indicate that the closer they are to English in their daily lives, both by frequently reading English articles, frequently watching English films, often listening to English music, the better the students' level of English speaking skills.